Rola telekomunikacji w logistyce organizacji sieciowych - Kozłowski, Remigiusz (Role of Telecommunication in Logistics of Network Organizations, 2005)
The article presents the role of telecommunication services in working and developing logistic processes in network organizations. It presents possibilities of using stationary, mobile and satellite telecommunication nets. The information about variety existing telecommunication solutions could help to make proper selection, which will permit to improve working logistics at organizations.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1078, s. 309-315